(untitled) (Circe de clásicos y modernos, 2018)
Commentaries were the most important way of philosophical production from the end of Hellenism up to late Antiquity. The richness and depth of this production was decisive not only for its historical value but also for its influence in later thought. Our intention is to explore the most significant aspects of this evolution recognizing its importance not only as sources of Plato’s work and fundamentally of Aristotle –the central figure in the development of this gender– but also as works with their own philosophical value. Through a schematic overview of its history: from its origins within aristotelianism to the appropriation by Christian hermeneutics, we will identify the philosophical interests that determined the appropriation of the texts in every phase.